Next generation diagnostics of cystic fibrosis and CFTR-related disorders by targeted multiplex high-coverage resequencing of CFTR. Issue 7 (17th May 2013) - Trujillano, D; Ramos, M D; González, J; Tornador, C; Sotillo, F; Escaramis, G; Ossowski, S; Armengol, L; Casals, T; Estivill, X
Abstract : Background: Here we have developed a novel and much more efficient strategy for the complete molecular characterisation of the cystic fibrosis (CF) transmembrane regulator ( CFTR ) gene, based on multiplexed targeted resequencing. We have tested this approach in a cohort of 92 samples with previously characterised CFTR mutations and polymorphisms. Methods: After enrichment of the pooled barcoded DNA libraries with a custom NimbleGen SeqCap EZ Choice array (Roche) and sequencing with a HiSeq2000 (Illumina) sequencer, we applied several bioinformatics tools to call mutations and polymorphisms in CFTR . Results: The combination of several bioinformatics tools allowed us to detect all known pathogenic variants (point mutations, short insertions/deletions, and large genomic rearrangements) and polymorphisms (including the poly-T and poly-thymidine-guanine polymorphic tracts) in the 92 samples. In addition, we report the precise characterisation of the breakpoints of seven genomic rearrangements in CFTR, including those of a novel deletion of exon 22 and a complex 85 kb inversion which includes two large deletions affecting exons 4–8 and 12–21, respectively. Conclusions: This work is a proof-of-principle that targeted resequencing is an accurate and cost-effective approach for the genetic testing of CF and CFTR -related disorders (ie, male infertility) amenable to the routine clinical practice, and ready to substitute classical molecular methods in medical genetics.